2018
DOI: 10.1016/j.intman.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Stakeholders Through Corporate Political Activity: Insights From MNE Nonmarket Strategy in an Emerging African Market

Abstract: For guidance on citations see FAQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 119 publications
0
32
0
5
Order By: Relevance
“…CPA draws from the tradition that firm performance is a function of its institutional contexts, which are informed and shaped by influential politicians, politics, and policies (Mbalyohere and Lawton, 2018). As such, CPA involves a set of strategies through which the firm aligns with its business environment and or institutional context to enhance its performance.…”
Section: Beyond Csr: Taking Corporate Political Responsibility Seriouslymentioning
confidence: 99%
“…CPA draws from the tradition that firm performance is a function of its institutional contexts, which are informed and shaped by influential politicians, politics, and policies (Mbalyohere and Lawton, 2018). As such, CPA involves a set of strategies through which the firm aligns with its business environment and or institutional context to enhance its performance.…”
Section: Beyond Csr: Taking Corporate Political Responsibility Seriouslymentioning
confidence: 99%
“…There are costs to these, since they are unlikely to be as efficient as an unfettered market operating in a perfectly defined environment, but they may offer a second-best solution (Rothaermel, 2001). Moreover, IVs can also trigger strategic responses, such as developing and strengthening business group affiliates (Manikandan and Ramachandran, 2015), and foster international learning efforts in emerging economies (Adomako et al, 2019), as well as nonmarket strategies (Cantwell, Dunning and Lundan, 2010;Mbalyohere and Lawton, 2018;Rao-Nicholson et al, 2019). In addition, the prevalence of IVs can force a firm to construct substitutes to compensate for the challenges in the business environment (Boddewyn and Doh, 2011;Peng et al, 2009).…”
Section: Resource Dependency Theorymentioning
confidence: 99%
“…Accordingly, previous studies have already shown that the effectiveness of MNEs in compensating the inability of host country institutions to provide electricity is strongly influenced by the proximity between the formal institutional context of the country of origin of the MNE and the formal institutional environment of the host country (D'Amelio et al, 2016). When formal institutions of the host and the home country presents some similarities, MNE managers are likely to have already developed at home the capability to deal with weak formal institutions, the resilience against and the adaptability to the political turbulences and uncertainties in the region (Mbalyohere and Lawton, 2018), and are more effective in identifying key actors to form winning coalitions in the host country (Cuervo-Cazurra and Genc, 2008;Holburn and Zelner, 2010;De Beule et al, 2014).…”
Section: H1 the Presence Of Fdi And Mnes Is More Likely To Positively Impact The Access To Electricity Of The Local Population When Both mentioning
confidence: 99%